IUFRO International Seminar-Workshop toward better management practices in tropical humid forests : developing principles and recommendations for the Amazon Basin - Sist, Plinio; Garcia-Fernandez, Carmen; Sabogal, César (BOIS & FORETS DES TROPIQUES, 2005)
Le résumé en français est disponible dans le fichier PDF de l'article. Organized under the auspices of the International Union of Forestry Research Organizations (IUFRO), the international seminar-workshop Towards better management practices in tropical humid forests: developing principles and recommendations for the Amazon Basin was held in Belém do Pará, Brazil (14-19 November 2004). (Résumé d'auteur)